Non-Pharmacological Therapy for Atrial Fibrillation: Managing the Left Atrial Appendage - Sushil Allen Luis; Damian Roper; Alexander Incani; Karl Poon; Haris Haqqani; Darren L. Walters (Cardiology Research and Practice)
The prevalence of atrial fibrillation (AF) is increasing in parallel with an ageing population leading to increased morbidity and mortality. The most feared complication of AF is stroke, with the arrhythmia being responsible for up to 20% of all ischemic strokes. An important contributor to this increased risk of stroke is the left atrial appendage (LAA). A combination of the LAA's unique geometry and atrial fibrillation leads to low blood flow velocity and stasis, which are precursors to thrombus formation. It has been hypothesized for over half a century that excision of the LAA would lead to a reduction in the incidence of stroke. It has only been in the last 20–25 years that the knowledge and technology has been available to safely carry out such a procedure. We now have a number of viable techniques, both surgical and percutaneous, which will be covered in this paper.